The Intersection of Generative AI and Applied Linguistics in Modern Marketing & Advertising Practices - Koswara, Asep (Cipta Pustaka Nusantara, 2025)
This study explores the intersection of generative AI and applied linguistics in modern marketing and advertising. Generative AI has revolutionized content creation by enabling hyper-personalization, optimizing audience engagement, and improving linguistic adaptability. Using a qualitative research methodology, this study employs content analysis and case studies to examine AI-driven marketing strategies, their implications on consumer behavior, and the ethical considerations surrounding automated content generation. While AI offers efficiency and innovation, challenges such as linguistic biases and ethical transparency persist. The study highlights advancements in natural language processing, the role of AI in shaping persuasive messaging, and the necessity for responsible AI implementation. Through an in-depth analysis, the research underscores the need for continued development in AI-human linguistic collaboration, ensuring inclusivity and authenticity in AI-generated marketing. Future prospects include the integration of multimodal AI, creating more immersive and interactive marketing experiences. The findings contribute to a deeper understanding of AI’s role in marketing, offering insights into its evolving impact on advertising communication and consumer interaction.